Preventing violence and enhancing mental health among clients of an invitro fertilization clinic in Jordan: results of a pre/post pilot test of the use of cognitive behavioral therapy - Cari Jo Clark; Zaid Al-Hamdan; Hala Bawadi; Hussein Alsalem; Jehan Hamadneh; Adnan Abu Al-Haija; Alexandria Ree Hadd; Rachael A. Spencer; Irina Bergenfeld; Rachel Hall-Clifford (BMC, 2024)
Abstract Introduction Infertility increases women's risk of intimate partner violence (IPV). Cognitive behavioral therapy (CBT) is commonly used to treat mental health problems among fertility treatment seeking patients. CBT has not been tested for its potential to reduce IPV in this population. We pilot test the use of CBT to prevent IPV and improve patients' mental health in a fertility clinic in Jordan. Methods Of 38 eligible fertility-treatment seeking couples, 16 consented and underwent up to 11 CBT sessions (average = 9) over 3 months. Interviews at baseline and 16 weeks post intervention (endline) assessed IPV, quality of life, social support, coping, and fear of spouse. Wilcoxon signed-rank and McNemar's tests were used to assess change in outcomes. Results At baseline, women's rates of IPV, depression, and anxiety were 75%, 87.5%, and 75% respectively, whereas men's rates of depression and anxiety were each 80%. Average baseline post-traumatic stress disorder (PTSD) symptoms for men and women were 3.3 and 2.7 respectively out of 5. IPV decreased 25% after treatment, and women reported less spousal fear. For both men and women, depression, anxiety, and PTSD symptoms decreased and social support and fertility quality of life improved. Conclusion Psychosocial support should be standard of care for the treatment of infertility given the burden of mental health problems and IPV and the utility of CBT in this patient population. Co-design with couples is needed to identify strategies to bolster participation along with population-based interventions to combat the stigma of infertility and mental health service use and enhance women's status.